Design and Implementation of a Blockchain-based Shipment Tracking Proof-of-Concept for Academic Application - Andi Arniaty Arsyad; Riri Safitri; Winangsari Pradani; Nurbojatmiko Nurbojatmiko; Abdullah Abdullah (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
The demand for secure, transparent shipment tracking is rising as digital logistics advances. Traditional centralized tracking systems face issues such as data delays and manipulation, which reduce trust and accuracy. This research aims to create a blockchain-based shipment-tracking system that serves as both a prototype and an educational tool for students. The system features a user interface built with Vue.js and utilizes a middleware layer with Node.js and Express.js. A smart contract in Solidity is deployed on a local Ethereum network using the Hardhat framework. This prototype allows students to engage with decentralized application development and explore interactions among front-end components, middleware, and smart contracts. Each transaction is recorded immutably, with an average gas consumption of about 175,000 units and execution times under 2 seconds, while preventing duplicate shipments. This research offers a functional shipment-tracking model that provides transparent data recording and serves as an effective framework for blockchain education, bridging theoretical concepts with practical applications in higher education.Keywords – Academic Application, Blockchain, Shipment Tracking, Smart Contract, Solidity.